ANALISIS SEMIOTIKA PADA LUKISAN DIGITAL SMUDGE ART K.H. ANWAR MANSHUR KARYA BAJU SENO HARTYANTO - Miqdam Abror; Ropingi; Khaerul Umam (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2018)
Digital painting are alternative media that show visual messages which element of da’wahput into the painting. With digital painting, we can share da’wah with the precious look. One of them is smudge art technic from Baju Seno that choose K.H. Anwar Manshur as an object. As we know that “Yai Anwar Manshur” is Caretaker of Lirboyo Kediri Boarding School. This research has goals to describes the signs that appear from smudge art digital painting and also to describe the meaning inside. The research use qualitative approach. The writer use analytical method with Charles Sanders Pierce Semiotic Theory. With use Semiotic Theory, any signs will prefers to “Yai Anwar Manshur”. And all of the verbal and nonverbal signs have to interpretate to be understood. The most important source of data is derived through the signs that appear on the smudge art digital painting of “Yai Anwar Manshur” and the previous research result on same themes, books, and also journals. There are signs that appear in smudge art digital painting “Yai Anwar Manshur” from Baju Seno. Start from nonverbal signs that appear on facial expressions, body expressions, and gestures of “Yai Anwar Manshur” as objects. And also visual signs as like design elements, for example lines or scratches effect of smudge tool, color, texture, and gradation that appear in smudge art digital painting “Yai Anwar Manshur”. The meaning or interpretation of nonverbal and visual signs that appear, are related with “Yai Anwar Manshur” as digital painting objects. In terms of attitude and personality, it is depicted in sign that appear on the smudg art digital painting by Baju Seno Hartyanto. Firm, disciplined, simple, and humble attitudes also personalities are the meanings that appear behind nonverbal and visual signs in digital painting. And form here the person or figure of “Yai Anwar Manshur” can be a motivation while encouraging everyone to be positive and be a better personality. The message can be a da’wah for the generations of Muslims around, through a visual work in the from of smudge art digital painting with objects “Yai Anwar Manshur” by Baju Seno Hartyanto.